2014
DOI: 10.4236/ojfd.2014.42015
|View full text |Cite
|
Sign up to set email alerts
|

Multimoment Hydrodynamics in Problem on Flow around a Sphere: Entropy Interpretation of the Appearance and Development of Instability

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…The multimoment hydrodynamics equations were used to study the phenomenon of instability appearance and development in the problem of flow around a solid sphere at a wide range of Reynolds number values (Lebed, 1997;1998;2014a;2014b). It was found that solutions to these equations lead the development of instability in the direction compatible with experiment.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The multimoment hydrodynamics equations were used to study the phenomenon of instability appearance and development in the problem of flow around a solid sphere at a wide range of Reynolds number values (Lebed, 1997;1998;2014a;2014b). It was found that solutions to these equations lead the development of instability in the direction compatible with experiment.…”
Section: Introductionmentioning
confidence: 98%
“…They are the disintegration of the Gibbs ensemble (Lebed, 1997;2014b), the breakage of unstable solution (Lebed, 1997;2014b), the movement of a system at an extremely unlikely direction described by the reverse multimoment hydrodynamics equations (Lebed, 2014b;2014c;2015b).It was discovered that system entropy begins to play the key role to predict the direction of instability development. The calculation of the system evolution becomes impossible without participation of the entropy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The problems encountered by classic hydrodynamics when interpreting observed evolution of unstable process, are proposed to be solved on the way toward an increase in the number of principle hydrodynamic values [4]. In [5]- [8], the multimoment hydrodynamics equations are used to study the phenomena of instability appearance and development in problem on flow around a solid sphere at a wide range of Reynolds number values.…”
Section: Introductionmentioning
confidence: 99%
“…The studies [5]- [8] demonstrated that when interpreting each of unstable regimes in problem on flow around a sphere the need emerges to involve the so-called reverse multimoment hydrodynamics equations [9]. The evolution of the system after losing its stability that is described by the direct hydrodynamics equations advances in direction of the system departure from the statistical equilibrium state.…”
Section: Introductionmentioning
confidence: 99%